Rozwój produktu markowego turystyki na terenach wiejskich - Brelik, Agnieszka (Development of Branded Product of Tourism in Rural Areas, 2005)
The paper presents the main role of tourism with special regards of rural tourism as a crucial factor development of rural areas. The author concentrates on issues connected with branded product of tourism with special regard to West Pomeranian Region, highlighting strong and weak sides of a product and chances and risks of its development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 70-77